Karakterisasi Fisik dan Mekanik Papan Komposit Serat Kelapa dan Limbah Plastik Pet Mengacu pada Standar SNI 03-2105-2006 - OKTA VIANO, RIO; Marthiana, Wenny; Arman, Rizky (Mesin, 2025)
This study aims to determine the physical and mechanical properties of composite board (density, moisture content, thickness swelling, elastic modulus and fracture modulus) of coconut fiber and PET polyethylene etilen terephalate plastic waste by referring to the SNI 03-2105-2006 standard with four comparison of coconut fiber composition : PET plastic : 157 yukalac resin (0:0:100; 5:5:90; 10:10:80; and 20:20:60) %. This research was conducted by varying the composition of coconut fiber, PET plastic and 157 yukalac resin, then tested the physical properties and mechanical properties of the composite board, the test parameters were density, moisture content ranged from 1.1026 to 1.1419 gr/cm³, moisture content ranged from 0.7379 to 2.3597 %, thickness development ranged from 0.326 to 0.602 %, the modulus of elasticity ranged from 5,566.71 to 34,317.48 kgf/cm², and the fracture modulus ranged from 153.34 kgf/cm² to 447.02 kgf/cm². The conclusion from the results of the tests carried out is that the more coconut fiber and PET plastic are added, the better the physical and mechanical properties are, in general the resulting composite board meets SNI 03-2105-2006 standards except for density.